"They have put a rope around my neck by bringing me here”: a historical exploration of witchcraft trials in the Transkeian Territories, 1882-1906 - Van der Merwe, Nicole (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.